The Role of c-Abl Kinase in Cancer Cells Sensitivity to Mitoxantrone - Siddiqui, Arafat (fi=Turun yliopisto|en=University of Turku|, 2018)
Triple-negative breast cancer (TNBC) is a cancer sub-type with poor prognosis and it lacks targeted therapies. The c-Abl is a non-receptor tyrosine kinase as well as a proto-oncoprotein. It has a role in DNA damage cascade which leads to either apoptosis or DNA repair. The effect of c-Abl can be enhanced by adjuvant therapy with DNA damage-inducing agents e.g. mitoxantrone. BRCA1 maintains genome integrity and controls DNA repair by homologous recombination. BRCA1 mutation is often found in TNBC. Three cell lines, cervical cancer cell line HeLa, BRCA1-wt TNBC cell line MDA-MB-231 and BRCA1-mutant TNBC cell line HCC-1937, were used. Cell viability analysis, cell cycle profiling by flow-cytometry, microscopic imaging, and BRCA1 silencing and Western blot analysis were done to investigate the effect of imatinib, a c-Abl inhibitor and mitoxantrone combination. The IC50 doses of mitoxantrone with and without imatinib were determined. Imatinib and mitoxantrone showed synergistic effect on cell viability in HeLa, MD-MB-231 and HCC-1937 cell lines. The combination causes more G2 arrest in HeLa cells (BRCA1-mutant) and MDA-MB-231 (BRCA1-wt) at low dose. The combination causes more G1-S arrest in BRCA1-wt TNBC cells at IC50 dose compared to mitoxantrone. However, there is more G1-S accumulation in BRCA1-silenced MDA-MB-231 cells with combination but more S-G2 accumulation with mitoxantrone compared with control siRNA MDA-MB-231 cells. Further studies are needed to investigate the mechanisms of c-Abl inhibition on DNA repair. The findings may contribute to the development of TNBC therapy.